Logistics as an Integrative Management Function – The Focus of Contemporary Management - Zekić, Zdravko (Oeconomica Jadertina, 2017)
A dynamic technological development that promotes the dynamics of the overall environment imposes, as a condition of survival, a flexible and adaptable, or dynamic behaviour of a modern enterprise in accordance with changing business conditions. Traditional business management focused on the efficiency of the qualitative transformation processes (production), the organizational structuring and optimization of the status of separate business subsystems in order to optimize the functioning of enterprises as a system, cannot, due to the recent condition of permanent discontinuous changes, result in a successful modern enterprise. A targeted network linking of all processes through the logistics system into a value creation system - a company as a socio-economic system of the environment highlights the holistic approach and the orientation towards flows as the basis for the dynamic optimization of modern business operations. Logistic management as a model for controlling space-time transformations of goods, energy, information and knowledge through qualitative transformation processes of an enterprise, according to the needs of the users and the goals of the enterprise, is simply imposing itself as an area of exploration of the possibilities to increase the success of modern business operations. The paper explores the potential for success which is derived from the application of the logistic concept of management and the perspective for the development of the competitiveness of enterprises by focusing on logistics as a management function within the globalized environment of permanent discontinuous changes.
Keywords: logistics; logistic management; optimization; efficiency; effectiveness